Workplace violence towards nurses: An act of remorse upon Feminity - Saleema Shoukat Ali Jassani (International Journal on Women Empowerment, 2015)
An intimidating work environment, in which insulting or obnoxious comments, persistent criticism or even physical abuse and threats triumph, is a reality for many employees in both public and private organizations. One novice RN was dealing with a patient in private ward of tertiary care hospital with a 35 year old male patient encountered with physical abuse when the patient touched her one of the private body part while performing IV cannulation. She also experienced unpleasant remarks and dirty gestures of patient as well as his relatives. As the incident took place she immediately stopped doing cannulation and started leaving room but was stopped by the relative and she has to tolerate aggression that she is incompetent which leads her to post traumatic stress syndrome. Violence towards nurses has been seen a major issue in both developing and developed countries and is increasing progressively in society and workplace.